Prevalence of childhood immunization defaulters and its associated factors among children in child care centers in Petaling District, Selangor, Malaysia - Krishna Moorthy, Damyanthy (2018)
Background: Immunization is an effective public health intervention to reduce morbidity and mortality among children and it will become more effective if the child can receive the full course of recommended immunization doses. However this, due to various factors many mothers default the immunization schedule for their children. Objective: The objective of this study was to determine the prevalence of childhood immunization defaulters and its associated factors among children below five years attending registered child care centers in Petaling district, Selangor. Methodology: A cross sectional study was conducted among mothers with children below five years from 60 registered child care centers in District of Petaling, Selangor. The data were collected from 1st July 2016 to 31st December 2016. The sample size was 1015, calculated based on two group comparison formula. The sampling technique used was cluster random sampling whereby the child care centers were randomly selected using the 3 digit table of random numbers. All mothers of children below five years in the selected child care centers who fulfilled the inclusion criteria were recruited for the study. The dependent variable was immunization defaulters. The independent variables were socio-demographic characteristic, immunization health facility characteristics, sources of immunization information, mother’s knowledge on immunization, attitude towards immunization, perceived health institution support and perceived barriers. A self-administered pretested questionnaire was used as the instrument for this study. The data were analyzed using the Statistical Package for Social Sciences (SPSS) version 22. Simple Logistic Regression, Chi-square or Fisher’s exact test were performed to determine the association between individual categorical variables and childhood immunization defaulters. Multivariate logistic regression was used to determine the predictors of childhood immunization defaulters. Results: The response rate was 67%. The prevalence rate for defaulting immunization was 20.7%. Based on the analysis of simple logistic regression, 24 variables that were significantly associated with immunization defaulters were mother’s age, ethnicity, religion, marital status, educational level, working status, family size, number of children, child’s age, child’s gender, child’s birth order, place of immunization, distance to health facility, travelling time to health facility, delayed immunization schedule, mass media, internet, health care professionals, knowledge on vaccine preventable disease, knowledge on side effects of immunization, knowledge on immunization contraindication, attitude towards childhood immunization, perceived health institution support and perceived barriers on childhood immunization. Multivariable analysis showed that the significant predictors of immunization defaulters were Non-Malay (AOR= 1.747, 95% CI = 1.214 - 2.514), single, divorced or widowed (AOR= 9.832, 95% CI = 2.440 - 39.623), diploma and below (AOR= 1.856, 95% CI = 1.151 - 2.994), 3 to 4 children (AOR= 1.789, 95% CI = 1.227- 2.609), children aged 2 years and below (AOR= 1.716, 95% CI = 1.161 - 2.536), travelling time of 30 minutes and above to health facility (AOR= 2.569, 95% CI = 1.603 - 4.119), had delayed immunization schedule (AOR= 2.599, 95% CI = 1.793 - 3.767), poor knowledge on vaccine preventable disease (AOR= 1.970, 95% CI = 1.358 - 2.857) and poor knowledge on immunization contraindications (AOR= 0.604, 95% CI = 0.419 - 0.869). Conclusion: The prevalence of childhood immunization defaulters in registered child care centers in Petaling District was 20.7%. The significant predictors were Non-Malay, single, divorced or widowed mothers, diploma and below, 3 to 4 children, children aged 2 years and below, travelling time of 30 minutes and above, had delayed immunization schedule, had poor knowledge on vaccine-preventable disease and poor knowledge on contraindication of immunization.